The Influence of Quality Academic Service on Student Satisfaction (Empiric Study on Bidikmisi Scholarship Students Regional Office of Universitas Terbuka at Pangkalpinang, Indonesia) - Mr Yusuf (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
This study aims to analyze the influence of the quality of academic service to the satisfaction student regional office of Universitas Terbuka (UPBJJ-UT) Pangkalpinang. The research method used is survey method. Type of research that is verification and descriptive. Data collection conducted through interviews and distribution of questionnaires. Multiple linear regression test obtained Y = 0,629 + 0,237X1 + 0,224X2 + 0,366X3 + 0,254X4 + 0,506X5 + E, multiple correlation test obtained (R) 0,919 and determination coefficient (R2) 84,5% and the rest (E) 15,5% influenced by other factors that are not examined the author. The value of F- count is greater than F-table (101,049>2,31), so it is stated that there is the significant hypothesis. It can be concluded that the quality of service simultaneously has a positive and significant effect on student satisfaction. Partially tangibles, empathy, reliability, responsiveness, assurance have the positive and significant effect on student's satisfaction at UPBJJ-UT Pangkalpinang.